Chemistry of the climate system volume 2: History, change and sustainability - Möller, Detlev 1947- (De Gruyter, 2020)
Climate change is a major challenge facing modern society. The chemistry of air and its influence on the climate system forms the main focus of this book. Vol. 2 of Chemistry of the Climate System takes a problem-based approach to presenting global atmospheric processes, evaluating the effects of changing air compositions as well as possibilities for interference with these processes through the use of chemistry